A review on production, application, and toxicological analyses of nanocrystalline cellulose as a novel fat replacer food additive - A., Aida Safina; N. L., Chin; I., Nur Akmal; M. Y., Nor Nadiah; Y., Yus Aniza (Rynnye Lyan Resources, 2022)
Nanocrystalline cellulose has gained much attention from the researcher. It provides many applications such as polymer additive, packaging, and tablet filler. This review established the recent isolation method of nanocrystalline cellulose from agricultural by-products, aiming to reduce waste that will affect the environment. The current nanocrystalline cellulose application as a food additive in many food products and its toxicological analyses was discussed. This work can be used as a guideline by researchers and food manufacturers to isolate nanocrystalline cellulose from agricultural waste and its use as a fat replacer in food products.